Religion-Based Science Modul on Human Circulatory System (Universitas Negeri Semarang, 2020)
The separation of religious values ​​from the substance of science learning is the main problem experienced by Islamic Based Schools with Integrated Curriculum. This causes disharmony relations between the subjects diniyah and general. So students are not able to get a rational understanding of Natural Sciences supported by the Qur'anic and Sunnah propositions. Planting religious values ​​through the application of the Learning Module is expected to be able to contribute maximally to the learning outcomes of students. The purpose of this study was to determine the effectiveness of the learning module to improve student learning outcomes. This study uses a research and development approach (R&D). The fund is through three stages namely; introduction, development and validation, by testing the experimental and control class using modules as the difference variables. The results of the study prove that the module is suitable for use in learning based on expert validation of 95%, teacher responses by 85.2%, student responses 84%, the average difference test of two classes is 0.0011 with alpha 0.05 which means that the differences in learning outcomes between the two classes significant. This proves that the use of natural science modules in the Human Blood Circulatory System material can improve student learning outcomes in class VIII SMPIT ITTIHADUL MUWAHIDIN Pati